The The Role of Purchase Intention as a Mediator in the Relationship Between Healthy Lifestyle and Social Media Marketing on the Purchase Decision of Pawon Ibun’s Tempe Broth Products - Sani, Evina Nahdiya; Andriani, Dwi Retno; Laili, Fitrotul; Syafrial, Syafrial (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 19 No 2 (2025): Vol 19 No 2 (2025), 2025)
This study is grounded in the increasing public awareness of healthy lifestyles in the post-pandemic era. On the other hand, social media platforms such as Instagram hold significant potential in influencing consumer behavior toward healthy products. However, the sales of Kaldu Tempe have shown a substantial decline despite its alignment with healthy lifestyle values. This study aims to: (1) identify the consumer characteristics of Kaldu Tempe Pawon Ibun; (2) analyze the relationship between healthy lifestyle and social media marketing on the purchase decision of Kaldu Tempe Pawon Ibun; and (3) examine the mediating role of purchase intention in the relationship between healthy lifestyle and social media marketing on the purchase decision of Kaldu Tempe Pawon Ibun. The research employed a quantitative explanatory approach with a sample size of 100 respondents. Descriptive statistics were used to address the first objective, while Structural Equation Modeling with Partial Least Squares (SEM-PLS) using SmartPLS 4 software was utilized to address the second and third objectives. The results indicate that adopting a healthy lifestyle significantly influences purchase decisions, both directly and indirectly through purchase intention. Social media marketing plays a critical role in fostering purchase intention, which in turn affects consumer decision-making, even though it does not have a direct impact on the purchase itself. These findings underscore the crucial role of purchase intention as a bridge between promotional efforts and consumer actions. This study provides strategic implications for micro, small, and medium enterprises (MSMEs) in designing promotional content that aligns with healthy lifestyle values to enhance consumer purchase intention and decisions.